Who is an internal migrant? - Rasadhika Sharma; Ulrike Grote (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2019)
There is no internationally accepted definition of an internal migrant. Different surveys and academic papers use varied definitions that are open to subjectivity. Our paper stresses this issue and tests the sensitivity of results obtained by econometric analysis to the use of different defining criterion. Using four definitions of an internal migrant based on aspects of varied time intervals, purpose of migration and geographical shifts, we examine the determinants of the migration decision and the impact of migration on the household's income. We employ Probit modelling and difference-in-difference Probability Score Matching to estimate the two questions, respectively. We find that a change in definition alters the target sample and therefore induces identification errors. In case of determinants, the magnitude and significance of variables capturing human and social capital, socio-demography and wealth of the household change across the four definitions. Additionally, having a migrant, increases the household's income under two definitions, while negatively impacting the household's income under the other two definitions. Therefore, it is pertinent to standardize the definition of an internal migrant before assessing the impact of migration. Our paper aims to bring this issue to the attention of international organizations and future researchers who work in the area of migration. It advocates for a standardized definition by proposing basic guidelines.
Keywords: O15; R23; J61; I32; O53; 330; Internal migration; Internal migrant; Vietnam; Measurement